Diagnosing computer hardware failures using expert system (rule-based technique) - Md Mustaffa, Mazlina; Shibghatullah, Abdul Samad; Hasan Basari, Abd Samad; Hussin, Burairah (Publications International, 2014)
This on-going study introduces a method that reduces the problems in diagnosing computer hardware failures. An expert intelligent system using the rule-based technique is introduced to diagnose computer hardware failures. The user or computer technician does not need to check parts of the computer hardware individually. They just need to key-in parts of the computer hardware and the symptoms into the system, and then it will diagnose the computer hardware failure. The development of the diagnosed computer hardware failure diagnosis using the rule-based technique is based on the expert system development methodology that consists of eight stages; Research and Review, Conceptualisation, Problem Assessment, Knowledge Acquisition and Analysis, Design and Implementation, Testing, Documentation and Management. The system will display the possible causes and suggest a solution. The rules of the proposed expert system are in the form of if-then statements. The rule-based system itself uses a simple technique and it starts with a rule-based, which contains all of the appropriate knowledge encoded into If-Then rules. Categories of rule in this system are an audio, Hard Disk, keyboard, mouse, power supply, processor, start up, Serial ATA, USB device, printer, motherboard, CPU, RAM, peripheral, BIOS, Video Monitor and adapter, DVD drive and DVD/CD recording.